Effect of “Nutricase” Pencil Box–Based Nutrition on Knowledge and Attitudes Toward Healthy Snacking among Elementary School Students - Yardha, Sawfa; Fadjri, T Khairul; Ahmad, Aripin; Alfridsyah, Alfridsyah (JAND: Journal of Applied Nutrition and Dietetic, 2025)
School snacks play an important role in children’s health and nutritional status. However, many snacks consumed by school-aged children do not meet food safety and nutritional standards, thereby increasing the risk of health problems. Therefore, appropriate nutrition education media are needed to improve students’ knowledge and attitudes toward healthy snacking. This study aimed to determine the effectiveness of the Nutricase educational media in improving students’ knowledge and attitudes toward healthy snack consumption.This study employed a Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected using questionnaires, and both quantitative and qualitative data were obtained. The study sample consisted of 22 fourth-grade students selected using a total sampling technique. Data analysis was conducted using descriptive and inferential statistics, including the Wilcoxon signed-rank test to analyze knowledge and the independent t-test to assess attitudes. The validation results from material, media, and language experts indicated that the Nutricase media was categorized as very good. The results of the Wilcoxon test showed a significant difference between pre-test and post-test knowledge scores (p = 0.003; p < 0.05), while the t-test results also showed a significant improvement in students’ attitudes toward healthy snacking (p = 0.026; p < 0.05). It is expected that Nutricase can serve as an effective nutrition education tool to enhance students’ awareness of healthy snacking practices.